Video Games and Resilience: Science Explains Why Playing Zelda Is Good For Your Brain - Schriefer, Natalie (Inverse, 2023)
Available to players of any skill level — no Twitch subscribers required.
Keywords: dept.hhs

Nintendo Has a Silent Problem With ‘Zelda’ Film - Schriefer, Natalie; CNN, sexuality She has written for; Think, NBC News; Insider; HuffPost; others. (Bloomberg.com, 2023)
A movie based on the popular video game will be inherently difficult because its recurring protagonist doesn’t speak. And developers have long preferred to keep it that way.
Keywords: Culture; Design; Generic 1st 'SI' Future; MAMMA MIA; MICROSOFT CORP; Markets; NETFLIX INC; NINTENDO CO LTD; Video Games; Women; dept.hhs; view

Funny Women: Query Letter for My Totally Publishable Novel - Schriefer, Natalie (The Rumpus, 2023)
(The previous sentence demonstrates both my market awareness and my forward thinking.)
Keywords: dept.hhs

How A Book From 1985 Unexpectedly Changed My View On My Sexuality - Schriefer, Natalie (HuffPost, 2023)
“I expected a lot of things when I started the novel … but I didn’t think it would feel culturally relevant in 2023.”
Section: Culture & Arts
Keywords: dept.hhs

Opinion: The new Zelda has finally arrived. It’s time for a rethink on video games. - Schriefer, Natalie (CNN, 2023)
I was thrilled when Nintendo released “The Legend of Zelda: Tears of the Kingdom” in May. But the unfettered joy I feel playing Zelda today took me longer to acquire than all 900 Korok seeds. While my parents supported my playing video games growing up, so many others blamed them for ruining lives, writes Natalie Schriefer.
Keywords: dept.hhs

Driving Directions - Schriefer, Natalie (Word Sports, 2023)
START: END: Trumbull High School Sacred Heart University 72 Strobel Road
Keywords: dept.hhs

I Wrote About Not Shaving For A Month — And The Backlash Made One Thing Perfectly Clear - Writer, Natalie SchrieferGuest (HuffPost, 2023)
"Within an hour, I had a dozen emails. By the next morning, there were two dozen more — plus more than 100 Twitter notifications."
Section: HuffPost Personal
Keywords: dept.hhs

Author, Edit Thyself. - Schriefer, Natalie (ASEE Prism, 2023)
The article focuses on providing tips to academics for improving the quality and acceptance chances of their scholarly work during the publishing process. Topics discussed include the benefits of reading work aloud to catch errors, batching tasks like reviewing reference lists and in-text citations, and the importance of carefully formatting tables and figures according to publication guidelines.
Keywords: Editing; Oral reading; Punctuation; Tense (Grammar); dept.hhs

The First Step - Schriefer, Natalie (2023)
From a snowbank I watched the squirrel run.
Keywords: dept.hhs

Career trajectories of women faculty who became academic administrators - Vancour, Michele L. (Advancing Women in Leadership Journal, 2023)
Women faculty often view academic leadership as incompatible with their work-life balance, detracting from research and teaching commitments, resulting in a loss of autonomy and an abandonment of discipline, promoting change in their relationships with colleagues, and placing an increased emphasis on budgeting, regulations and compliance (DeZure et al., 2014). Many researchers suggest that institutional culture works against leadership development for faculty, making the transition from faculty to administrator unlikely (Barden & Curry, 2013). It is increasingly important to identify the key factors that make the difference for women faculty to assume these roles. As such, in this study qualitative methods were employed to examine the experiences and career trajectories of 16 academic women who held tenured, fully promoted faculty positions prior to becoming administrators. The researcher found evidence to support future recruitment and retention in higher education leadership.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed

The implementation of a nutrition intervention in food pantries: the spirit of SWAP - Morales, Sofia I.; Vicente, Genesis; LaMonaca, Katherine; Rios, Jasmine; Cunningham, Shayna D.; Higginbottom, Jackson; Mathios, Erin; Werlin, Steve; Cramer, James; Santilli, Alycia; O’Connor Duffany, Kathleen (Health Promotion Practice, 2023)
Background. Food insecurity, affecting approximately 10% of the U.S. population, with up to 40% or higher in some communities, is associated with higher rates of chronic conditions and inversely associated with diet quality. Nutrition interventions implemented at food pantries are an effective strategy to increase healthy food choices and improve health outcomes for people experiencing food and nutrition insecurity. Supporting Wellness at Pantries (SWAP), a stoplight nutrition ranking system, can facilitate healthy food procurement and distribution at pantries. Purpose. Guided by the RE-AIM Framework, this study assesses the implementation and outcomes of SWAP as nutritional guidance and institutional policy intervention, to increase procurement and distribution of healthy foods in pantries. Method. Mixed-methods evaluation included observations, process forms, and in-depth interviews. Food inventory assessments were conducted at baseline and 2-year follow-up. Results. Two large pantries in New Haven, Connecticut, collectively reaching more than 12,200 individuals yearly, implemented SWAP in 2019. Implementation was consistent prepandemic at both pantries. Due to COVID-mandated distribution changes, pantries adapted SWAP implementation during the pandemic while still maintaining the ?spirit of SWAP.? One pantry increased the percentage of Green foods offered. Challenges to healthy food distribution are considered. Discussion. This study has implications for policy, systems, and environmental changes. It shows the potential for SWAP adoption at pantries, which can serve as a guide for continued healthy food procurement and advocacy. Maintaining the ?spirit of SWAP? shows promising results for food pantries looking to implement nutrition interventions when standard practice may not be possible.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed